SEROPREVALENCE OF LEPTOSPIROSIS IN SHEEP FROM TWO FARMS IN PUNO, PERU - Bazay D., Gonzalo (2014)
The objective of the present study was to determine the seroprevalence ofLeptospira spp in two sheep farms in Puno, Peru. Blood samples (n=100) were collectedfrom March to May 2006 at the ILLPA Experminental Research Farm of INIA and theAsiruni farm. The samples were processed using the microscopic agglutinationserological test. The total prevalence was 57%, without differences between farms.